دراسة الأداء لليزر المضخ بواسطة الإشعاع الشمسي Ce/Cr/Nd: YAG lasers - دو محمد ضياء الدين – قيطوبي عثمان – تومي بالقاسم (university of eloued جامعة الوادي, 2024)
تعتبر منظومة الليزر الشمسي من أبرز الأنظمة الليزرية المستخدمة والتي تعمل علي استغلال الطاقة الشمسية المركزة في تحفيز الوسط الليزري الفعال، والعمل على تحسين مردودية الإشعاع الليزري الناتج يكون بعدة طرق مختلفة، والتي من أبرزها تحسين كفاءة الوسط الفعال المستخدم وتطوير خصائصه. تم في هذه المذكرة دراسة الأداء للوسط الفعال Nd:YAG) ) الأكثر استخداما وشيوعا وذي نسبة التطابق المنخفضة نسبيا مع طيف الانبعاث الشمسي% 16 وكذلك دراسة الأداء للأوساط المطعمة والمحسنة التالية والناتجة انطلاقا من الوسط الاول:(Nd:YAG)،(Cr :Nd:YAG) (Ce:Nd:YAG) ، (Ce:Cr:Nd:YAG) بينت نتائج المحاكاة والنمذجة العددية بواسط برنامجي ZemaxوLASCAD أن عمليات التطعيم المضاعف بواسطة أيونات السيريوم والكروم على حدا، والتطعيم المضاعف بكليهما في المرحلة النهائية أي الوسط (Ce: Cr :Nd:YAG) أدى إلى تحسينات ممتازة وجد معتبرة في خصائص الأوساط الفعالة الناتجة ، وبالتالي خصائص المنظومة الليزرية والمردود الليزري الناتج بالمقارنة مع المنظومة الليزرية التقليدية للوسط الاول (Nd:YAG) وتحت نفس الشروط المطبقة في الدراسة تم الحصول علي استطاعة امتصاص أكبر بـ 1.5 مرة عند التطعيم بالكروم, وبمقدار 1.98 مرة أكبر عند التطعيم بالسيريوم، وبقيمة 2.32 مرة أكبر عند التطعيم بكليهما, كما سجلنا ارتفاع كبير في قيمة الاستطاعة للانبعاث الليزري الناتج وكذا كفاءة التجميع، حيث ارتفعت قيمة الخراج الليزري بـ 1.66 مرة عند التطعيم بالكروم ، وبمقدار 2.33 مرة عند التطعيم بأيونات السيريوم، كما تضاعفت قيمة خراج الانبعاث الليزري وكذا كفاءة التجميع بمعدل ثلاث مرات مقارنة بالوسط الاول Nd:YAG ) )، أي بتحسينات ممتازة وجدّ معتبرة لمردود المنظومة الل) ions separately, and doubling doubling with both in the final stage, i.e. the medium (Ce:Cr:Nd:YAG), led to excellent and significant improvements in the properties of the resulting active media, and thus the properties of The laser system and the resulting laser yield Compared to the traditional laser system for the first medium (Nd:YAG), and under the same conditions applied in the study, an absorption capacity of 1.5 times greater was obtained when grafting with chromium, 1.98 times greater when grafting with cerium, and 2.32 times greater when grafting with both. We also recorded a significant increase in the power value of the resulting laser emission as well as the collection efficiency, as the value of the laser emission increased by 1.66 times when doping with chromium, and by 2.33 times when doping with cerium ions. The value of the laser emission output as well as the collection efficiency doubled by a rate of three times compared to the first medium, Nd. (YAG), that is, with excellent and significant improvements to the laser system’s efficiencyThe results of simulation and numerical modeling using the Zemax and LASCAD programs showed that the processes of double doping with cerium and chromium The solar laser system is considered one of the most prominent laser systems used, which works to exploit concentrated solar energy to stimulate the effective laser medium, and working to improve the yield of the resulting laser radiation is done in several different ways, the most prominent of which is improving the efficiency of the active medium used and developing its properties. In this memorandum, the performance of the active medium (Nd:YAG), which is the most commonly used and widely used and has a relatively low match rate with the solar emission spectrum of 16%, was studied, as well as the performance of the following grafted and improved media produced from the first mediumيزرية.
مدكرة ماستر فيزياء
Keywords: Nd:YAG ) ); Cr :Nd:YAG ) ); Ce :Nd:YAG ) ); Ce: Cr :Nd:YAG )) ، الليزر الشمسي، الوسط الفعال، نسبة التطابق، طيف الانبعاث الشمسي، التطعيم المضاعف، استطاعة الانبعاث الليزري.; (Nd:YAG ); (Cr :Nd:YAG ); (Ce :Nd:YAG ); Ce:(Cr :Nd:YAG) )Solar laser; Active medium; Matching ratio; Solar emission spectrum; double dopping; Laser emission power.